1 - Demystifying the Future in Africa’s (Un)vanishing Past: A Study of Ngugi wa Thiong’o’s Novels - Adeoti, Gbemisola (Africa Development, 2021)
This article attempts a critical analysis of Ngugi wa Thiong’o’s last two novels: Matigari and Wizard of the Crow. This is with a view to interrogating the novelist’s dissection of problems confronting post-independence African nations and how these nations can be re-invented. The analysis is done against the backdrop of growing challenges of neo-liberalism and Westernisation, otherwise known as globalisation.